PUBLIC ADMINISTRATION AND SUSTAINABLE DEVELOPMENT GOALS (SDGS): A LITERATURE REVIEW ON THE ROLE OF BUREAUCRACY IN SUSTAINABLE DEVELOPMENT, SOCIAL JUSTICE, AND POVERTY ERADICATION - Dila Erlianti; Adi Mursalin; Rosijanih Arbie (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to examine the role of bureaucracy in supporting the achievement of Sustainable Development Goals (SDGs), which include sustainable development, social justice, and poverty alleviation. Through a literature review, this study examines how public administration as a bureaucratic system plays a role in formulating, implementing, and evaluating inclusive and sustainable development policies. The findings show that bureaucracy has a strategic role as a coordinator and implementer of policies that must be able to innovate, adapt, and establish multisectoral partnerships to overcome various development challenges. However, obstacles such as fragmentation of implementation, limited human resource capacity, and lack of transparency remain major obstacles. Therefore, bureaucratic reform that prioritises accountability, digital technology, and public participation is crucial to optimising the role of the bureaucracy in achieving SDG targets effectively and sustainably.